Parathyroid Adenoma with Fibrous Dysplasia of Maxilla and Mandible in a Patient with End Stage Renal Disease (ESRD) on Routine Hemodialysis: A Case Report - Lumban Tobing, Richard Sumihar Hasudungan; Azhar, Yohana (Indonesian Journal of Cancer, 2024)
Introduction: End Stage Renal Disease (ESRD) can cause secondary hyperparathyroidism, resulting in parathyroid hyperplasia. In parathyroid hyperplasia, monoclonal development can occur, resulting in nodular hyperplasia. This nodular hyperplasia was thought to develop into a carcinoma, but its development into a benign neoplasm is very rare. This case report presents a parathyroid adenoma that developed in a patient with endstage renal failure who required routine hemodialysis. Case Presentation: A 31yearold woman presented with complaints of facial bone swelling, shortened body, and a previous history of renal failure with hemodialysis therapy since 4 years ago. From the blood test, a hyperparathyroid condition was found, and a history of hypocalcemia. A sestamibi (MIBI) examination has also been done with the results of bilateral inferior parathyroid adenomas. The patient was diagnosed with bilateral inferior parathyroid adenoma with endstage renal disease (ESRD) on hemodialysis and bilateral inferior parathyroidectomy was performed on the patient. The patient’s progress was followed from diagnosis, surgery, and followup after surgery. At 4 months postoperatively, the suspicion of a mass in the residual parathyroid was confirmed by parathyroid hormone (PTH) and MIBI examination. The patient was suspected to have parathyroid hyperplasia in the remaining gland, with risk factors for hyperparathyroidism due to ESRD. Conclusions: ESRDinduced secondary hyperparathyroidism may lead to enlargement of all parathyroid glands which may develop into nodules. Therefore, careful monitoring and diagnostics supported by hospital policy is required and removal of all parathyroid glands is considered in such patients, even if not all parathyroid glands have masses.